The Influence Of Layout And Display On Consumer Purchase Interest At JIFFINA - Sabila, Maharsi Anis; Prasetya, Juliasari; Shoffiyati, Peni; Sunardiansyah, Yogi Akbar; Broto, Taukhid Wisnu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
The JIFFINA 2023 exhibition is one of the prestigious events expected to stimulate economic growth in the Special Region of Yogyakarta and Central Java. In 2022, JIFFINA was held in August and successfully recorded transactions worth USD 24 million, with at least 2,000 buyers from various countries. This study investigates the influence of layout and display on consumer interest at the JIFFINA 2023 furniture exhibition. JIFFINA 2023 aims to attract a larger number of visitors compared to the previous year. To achieve this goal, the exhibition is required to enhance its overall quality. These enhancements are determined not only by the quality of the products but also by the effectiveness of their arrangement and presentation. Well-organized exhibition booths have the potential to draw more visitors and increase the likelihood of sales. This study employs a quantitative approach using multiple linear regression analysis. The findings are expected to provide a theoretical contribution to the study of purchase interest in furniture exhibitions and to support the development of the furniture industry in Indonesia.